Investigating the Factors Affecting the Properties of Coral Sand Treated with Microbially Induced Calcite Precipitation - Wenni Deng; Yue Wang (Advances in Civil Engineering)
Microbial-induced carbonate precipitation (MICP) can be used to cement coral sand to improve its engineering properties to protect coastal structures. In this study, a series of laboratory tests were conducted to test the effect of the MICP method by using an ureolytic bacterium (Sporosarcina pasteurii). In order to determine the activity of bacteria, the growth properties of the microbial strain were observed under different culture conditions (different pH and temperature). The effect of partial size distribution and nutrient concentration on the soil permeability and unconfined compressive strength was then examined in coral sand. The results showed that the pH had less effect on the bacteria growth compared to temperature. The bacteria can growth well at pH over 8 and temperature higher than 20°C. The well-degraded soil has higher unconfined compressive strength (1.91–2.61 MPa) than poor-degraded soil (1.31 MPa). The similar trend was also found in permeability reduction. The unconfined compressive strength increased as the biocement solution concentration increased to 1 mol/L and then decreased at 1.5 mol/L.